FENOMENA UANG DIGITAL - Teguh Permana; Andriani Puspitaningsih (Universitas Halu Oleo, 2019)
This study aims to determine the phenomenon of digital money that occurred in the past decade. The research method used is descriptive method and content analysis or content analysis. Broadly speaking, the systematic writing is more narrative that collects the opinions of experts, journals, books and writings published on the internet related to digital money. The results showed that digital money is a necessity of today's technological developments. The research findings imply that the government must be proactively involved in developing this digital money, not prohibited but regulated in cooperation with the central bank, in this case Bank Indonesia as a monetary authority in Indonesia.